A conserved regulatory program initiates lateral plate mesoderm emergence across chordates - Karin D. Prummel (Nature Portfolio, 2019)
Numerous tissues are derived from the lateral plate mesoderm (LPM) but how this is specified is unclear. Here, the authors identify a pan-LPM reporter activity found in the zebrafish draculin (drl) gene that also shows transgenic activity in LPM-corresponding territories of several chordates, including chicken, axolotl, lamprey, Ciona, and amphioxus.